Competitive positioning of German universities: Deliberate decision, fate, or fiction? - Uwe Cantner; Nils Grashof; Thomas Grebel; Anna Kosmützky; Georg Krücken; Xijie Zhang (Friedrich Schiller University Jena, Faculty of Economics and Business Administration, 2023)
With the increasing autonomy, the competitive pressure on German universities is rising. More freedom comes along with a higher obligation to position oneself in the (German) tertiary education and research market. We investigate to what extent a (competitive) positioning of German universities can be detected and how their positioning changes over time. Using non-parametric productivity estimation, we analyze 79 Germany universities based on information about the German University Statistics (Hochschulstatistik) provided by the German statistical office (Statistisches Bundesamt). Our (preliminary) results show that a clear positioning according to productivity statistics remains vague. The resulting competitive dynamics remains low, whereas the Excellence Initiative only induced an anticipation effect in the competitive dynamics. Overall, the scope of (most) universities for a competitive repositioning seems to be low.
Keywords: 330; Competition; German Universities; Efficiency; Positioning; DEA